The Influence of Gross Profit Margin and Return on Assets on Stock Prices in Jakarta Islamic Index 70 (2020–2024) - Bondan Estu Prabowo; Irwin Ananta Vidada (Manunggal Halim Jaya, 2026)
During the period from 2020 to 2024, the stocks in the Jakarta Islamic Index 70 (JII70) traded on the Indonesia Stock Exchange exhibited price movements believed to be influenced by companies' financial health. This research investigates how Gross Profit Margin (GPM) and Return on Assets (ROA) affect stock prices. Using a quantitative method, this study relies on secondary data from financial statements and stock price history, and employs purposive sampling to select 38 companies, generating 190 data points. The analysis was conducted using SPSS version 27 and multiple linear regression. The results show that GPM has a statistically significant adverse effect on stock prices, as evidenced by a t-statistic value of -2.500, which is below the critical t-value of 1.97569, and a p-value of 0.013, which is less than 0.05. Conversely, ROA does not show a significant effect on stock prices, as indicated by a t-statistic value of 1.449, which is below the t-table value of 1.97569, and a p-value of 0.150, which is greater than 0.05. However, when considered together, GPM and ROA have a significant impact on stock prices, with an F-statistic of 3.404 (greater than the F-table value of 3.06) and a p-value of 0.036 (less than 0.05).